The architecture of engagement: A qualitative study of gamification and the retention lifecycle in an Indian fitness app - A C Nigam; R S Chanda (Next Research, 2026)

Long-term manuring influences boron availability in an Inceptisol under rice–wheat cropping system - Prince Kumar; Ruma Das; Dibyendu Sarkar; Mandira Barman; Abir Dey; Y. S. Shivay; Mayurakshi Chanda; Shrila Das; S. P. Datta (Nutrient Cycling in Agroecosystems, 2026)

Tourists’ Circular Behavior and Its Determinants: Pathways Toward Sustainable Destinations - Swati Naik; Ruby S. Chanda (Circular Economy and Sustainability, 2026)

Facile fabrication of NiO/MnO2/CuO nanocomposite as robust electrode material for electrochemical water splitting - Atif Nazir; Chanda Sehar; Muhammad Fahad Saeed; Areej Fatima; Wael dheaa Kadhim; Zainab Ahmed Abass; Imran Shakir; Aboud Ahmed Awadh Bahajjaj; Muhammad Ali Khan; S. Shah (Fuel, 2026)

In silico design, synthesis of a novel chalcone derivative and its in vitro and in vivo anticancer activity against colon cancer-induced mouse model - Uday Raj Sharma; Sushavan Roy; Gurubasavaraja Swamy Purawargaar Matada; Manjunatha P M; Suresh Janadri; Surendra Vada; T. Haribabu; Nageena Taj; Gayathri S V; Rohit Pal; Susovan Das; Nirmal Chanda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

How estuaries modulate the riverine fluxes of copper (Cu) and cadmium (Cd) to seawater - Pratyusha Chanda; Sambuddha Misra; Tarun K. Dalai; Madeleine S. Bohlin; Emily I. Stevenson; Helen M. Williams (Chemical Geology, 2025)

Validation of technology for integrated management of pre- and post-harvest diseases of mango fruits - P. K. Shukla; S. Sriram; T. Naga Lakshmi; G. Sandeep Naik; Ankita Roy; Hemant Sharma; V. K. Bhalerao; A. K. Jain; Chanda Kushwaha; K. Mounika; R. A. Raut; Y. R. Gorekar (Indian Phytopathology, 2025)

Association of chronic arsenic exposure with cellular immune profile in MINIMat adolescents: A birth cohort in Bangladesh - Farjana Haque; Evana Akhtar; Bikash Chandra Chanda; Anjuman Ara; Md.Ahsanul Haq; Protim Sarker; Maria Kippler; Yukiko Wagatsuma; Ondine S. von Ehrenstein; Rubhana Raqib (Environmental Toxicology and Pharmacology, 2024)

Litter and soil biodiversity jointly drive ecosystem functions - Shengen Liu; César Plaza; Raúl Ochoa‐Hueso; Chanda Trivedi; Juntao Wang; Pankaj Trivedi; Guiyao Zhou; Juan Piñeiro; Catarina S. C. Martins; Brajesh K. Singh; Manuel Delgado‐Baquerizo (Global Change Biology, 2023)
The decomposition of litter and the supply of nutrients into and from the soil are two fundamental processes through which the above‐ and belowground world interact. Microbial biodiversity, and especially that of decomposers, plays a key role in these processes by helping litter decomposition. Yet the relative contribution of litter diversity and soil biodiversity in supporting multiple ecosystem services remains virtually unknown. Here we conducted a mesocosm experiment where leaf litter and soil biodiversity were manipulated to investigate their influence on plant productivity, litter decomposition, soil respiration, and enzymatic activity in the littersphere. We showed that both leaf litter diversity and soil microbial diversity (richness and community composition) independently contributed to explain multiple ecosystem functions. Fungal saprobes community composition was especially important for supporting ecosystem multifunctionality (EMF), plant production, litter decomposition, and activity of soil phosphatase when compared with bacteria or other fungal functional groups and litter species richness. Moreover, leaf litter diversity and soil microbial diversity exerted previously undescribed and significantly interactive effects on EMF and multiple individual ecosystem functions, such as litter decomposition and plant production. Together, our work provides experimental evidence supporting the independent and interactive roles of litter and belowground soil biodiversity to maintain ecosystem functions and multiple services.

Does preclinical analysis based on static loading underestimate post-surgery stem micromotion in THA as opposed to dynamic gait loading? - Adeline S. Vio War; Neeraj Kumar; Souptick Chanda (Medical & Biological Engineering & Computing, 2023)

Clay authigenesis in carbonate-rich sediments and its impact on carbonate diagenesis - Piyali Chanda; Arjun Kohli; Fang-Zhen Teng; Matthew S. Fantle (Geochimica et Cosmochimica Acta, 2023)

Analyzing influence of thermal and osmotic stress on native isolates of Fusarium oxysporum f.sp. cubense - S. Akhileswara Reddy; Chanda Kushwaha; Bishun Deo Prasad (Indian Phytopathology, 2022)

Differential response of Brn1 at varied thermal regimes and its relation with virulence and extracellular release of cellulase and amylase in Alternaria brassicicola - Diksha Sinha; Chanda Kushwaha; Ravi S. Singh; Chandan Kishore (Journal of Plant Pathology, 2021)

Outwelling of total alkalinity and dissolved inorganic carbon from the Hooghly River to the adjacent coastal Bay of Bengal - Jayashree Ghosh; Kunal Chakraborty; Abhra Chanda; Anirban Akhand; Trishneeta Bhattacharya; Sourav Das; Isha Das; Sugata Hazra; S. B. Choudhury; Mark Wells (Environmental Monitoring and Assessment, 2021)

Dynamics of morpho-physiological characteristics of Cassia tora L. (Fabaceae) in oil field pollution stress environment - B. Sarma; S. K. Chanda; P. R. Bhattacharyya; M. Bhuyan (International Journal of Environmental Science and Technology, 2019)

Genotyping-by-sequencing based genetic mapping reveals large number of epistatic interactions for stem rot resistance in groundnut - Sneha M. Dodia; Binal Joshi; Sunil S. Gangurde; Polavakkalipalayam P. Thirumalaisamy; Gyan P. Mishra; Dayama Narandrakumar; Pooja Soni; Arulthambi L. Rathnakumar; Jentilal R. Dobaria; Chandramohan Sangh; Annapurna Chitikineni; Sumitra V. Chanda; et al. (Theoretical and Applied Genetics, 2019)

Nutrient modeling of an urban lake using best subset method - J. K. Biswas; B. Bera; R. Chanda; S. K. Sarkar; J. Majumdar; S. Majumder; S. Hazra (International Journal of Environmental Science and Technology, 2018)

Effectiveness of omega-3 polyunsaturated fatty acids against microbial pathogens - Warren Chanda; Thomson P. Joseph; Xue-fang Guo; Wen-dong Wang; Min Liu; Miza S. Vuai; Arshad A. Padhiar; Min-tao Zhong (Journal of Zhejiang University-SCIENCE B, 2018)

Nano-inspired systems in food technology and packaging - Preetam Sarkar; Ruplal Choudhary; Shubham Panigrahi; Irshaan Syed; S Sivapratha; Chanda Vilas Dhumal (Environmental Chemistry Letters, 2017)

Genomic epidemiology of Cryptococcus yeasts identifies adaptation to environmental niches underpinning infection across an African HIV / AIDS cohort - Mathieu Vanhove; Mathew A. Beale; Johanna Rhodes; Duncan Chanda; Shabir Lakhi; Geoffrey Kwenda; Sile Molloy; Natasha Karunaharan; Neil Stone; Thomas S. Harrison; Tihana Bicanic; Matthew C. Fisher (Molecular Ecology, 2017)
Emerging infections caused by fungi have become a widely recognized global phenomenon and are causing an increasing burden of disease. Genomic techniques are providing new insights into the structure of fungal populations, revealing hitherto undescribed fine‐scale adaptations to environments and hosts that govern their emergence as infections. Cryptococcal meningitis is a neglected tropical disease that is responsible for a large proportion of AIDS ‐related deaths across Africa; however, the ecological determinants that underlie a patient's risk of infection remain largely unexplored. Here, we use genome sequencing and ecological genomics to decipher the evolutionary ecology of the aetiological agents of cryptococcal meningitis, Cryptococcus neoformans and Cryptococcus gattii , across the central African country of Zambia. We show that the occurrence of these two pathogens is differentially associated with biotic (macroecological) and abiotic (physical) factors across two key African ecoregions, Central Miombo woodlands and Zambezi Mopane woodlands. We show that speciation of Cryptococcus has resulted in adaptation to occupy different ecological niches, with C. neoformans found to occupy Zambezi Mopane woodlands and C. gattii primarily recovered from Central Miombo woodlands. Genome sequencing shows that C. neoformans causes 95% of human infections in this region, of which over three‐quarters belonged to the globalized lineage VNI . We show that VNI infections are largely associated with urbanized populations in Zambia. Conversely, the majority of C. neoformans isolates recovered in the environment belong to the genetically diverse African‐endemic lineage VNB , and we show hitherto unmapped levels of genomic diversity within this lineage. Our results reveal the complex evolutionary ecology that underpins the reservoirs of infection for this, and likely other, deadly pathogenic fungi.

Potential CO2 Emission Due to Loss of Above Ground Biomass from the Indian Sundarban Mangroves During the Last Four Decades - Anirban Akhand; Anirban Mukhopadhyay; Abhra Chanda; Sandip Mukherjee; Abhishek Das; Sourav Das; Sugata Hazra; Debasis Mitra; S. B. Choudhury; K. H. Rao (Journal of the Indian Society of Remote Sensing, 2017)

Blue Carbon Stock of the Bangladesh Sundarban Mangroves: What could Be the Scenario after a Century? - Abhra Chanda; Anirban Mukhopadhyay; Tuhin Ghosh; Anirban Akhand; Parimal Mondal; Subhajit Ghosh; Sandip Mukherjee; Judith Wolf; Attila N. Lázár; Md. Munsur Rahman; Mashfiqus Salehin; S. M. Chowdhury; et al. (Wetlands, 2016)

Mangrove associates versus true mangroves: a comparative analysis of leaf litter decomposition in Sundarban - Abhra Chanda; Anirban Akhand; Sudip Manna; Sourav Das; Anirban Mukhopadhyay; Indrani Das; Sugata Hazra; S. B. Choudhury; K. H. Rao; V. K. Dadhwal (Wetlands Ecology and Management, 2016)

A combined inverse method and multivariate approach for exploring population trends of Florida manatees - Chanda J. Littles; Sergei S. Pilyugin; Thomas K. Frazer (Marine Mammal Science, 2016)
Given the expense and time required to monitor marine mammal populations effectively, approaches that fully exploit the resulting data certainly are warranted. We employed a two‐step modeling approach to estimate key demographic parameters, including immigration, from aerial surveys of manatees ( Trichechus manatus latirostris ) in the Northwest management unit of Florida. Abundances of adults and calves were predicted by multivariate adaptive regression spline ( MARS ) models, after accounting for heterogeneous detection rates caused by variable environmental conditions. The resulting predictions were incorporated into a stage‐structured, deterministic model that used an inverse method to estimate parameters with and without immigration. The model without immigration estimated mean survival probabilities of 0.966, 0.923, and 0.794 for adults, subadults and calves, respectively, with a per capita reproductive rate of 0.135. These parameter estimates yielded an overall mean population growth rate of approximately 1.037, which is comparable to rates from mark‐recapture studies. When we added an immigration term that accounted for the greater slope in adult counts since 1999, as identified by the MARS model, the estimated per capita reproductive rate was 0.122, with survival probabilities for adults, subadults and calves of 0.926, 0.920, and 0.833, respectively. These rates were coupled with an estimated mean winter immigration rate corresponding to roughly 5.2% of the adult and subadult population. In this latter scenario, the number of manatees in the core population of the Northwest management unit was predicted to remain constant, with a population growth rate near one, and additional manatees counted during aerial surveys were deemed to be immigrants. While further studies could certainly expound on the potential effects of migrants on population indices, we present this first published immigration estimate for wintering manatees in northwest Florida.

A Review on Air Pollution Monitoring and Management Using Plants With Special Reference to Foliar Dust Adsorption and Physiological Stress Responses - S. S. Ram; S. Majumder; P. Chaudhuri; S. Chanda; S. C. Santra; A. Chakraborty; M. Sudarshan (Critical Reviews in Environmental Science and Technology, 2015)

A comparative immunological analysis of CoCl2 treated cells with in vitro hypoxic exposure - Shweta; K. P. Mishra; S. Chanda; S. B. Singh; L. Ganju (BioMetals, 2015)

Evaluation and Selection of Indicators for Land Degradation and Desertification Monitoring: Types of Degradation, Causes, and Implications for Management - Or. Kairis; C. Kosmas; Ch. Karavitis; C. Ritsema; L. Salvati; S. Acikalin; M. Alcalá; P. Alfama; J. Atlhopheng; J. Barrera; A. Belgacem; A. Solé-Benet; et al. (Environmental Management, 2014)

Evaluation and Selection of Indicators for Land Degradation and Desertification Monitoring: Methodological Approach - C. Kosmas; Or. Kairis; Ch. Karavitis; C. Ritsema; L. Salvati; S. Acikalin; M. Alcalá; P. Alfama; J. Atlhopheng; J. Barrera; A. Belgacem; A. Solé-Benet; et al. (Environmental Management, 2014)

Plant canopies: bio-monitor and trap for re-suspended dust particulates contaminated with heavy metals - S. S. Ram; S. Majumder; P. Chaudhuri; S. Chanda; S. C. Santra; P. K. Maiti; M. Sudarshan; A. Chakraborty (Mitigation and Adaptation Strategies for Global Change, 2014)

Traceless synthesis of diketopiperazine fused tetrahydro-β-carbolines on soluble polymer support - Kaushik Chanda; Cheng-Ting Chou; Jin-Ji Lai; Shu-Fen Lin; Gorakh S. Yellol; Chung-Ming Sun (Molecular Diversity, 2011)

Assessment of anti-inflammatory and hepatoprotective potency of Polyalthia longifolia var. pendula leaf in Wistar albino rats - A. Tanna; R. Nair; S. Chanda (Journal of Natural Medicines, 2009)

Antibacterial and preliminary phytochemical and physico-chemical analysis of Eucalyptus citriodora Hk leaf - Y. Vaghasiya; R. Nair; S. Chanda (Natural Product Research, 2008)

Radioimmunoassay of milk progesterone as a tool for fertility control in smallholder dairy farms - M. Shamsuddin; M. M. U. Bhuiyan; P. K. Chanda; M. G. S. Alam; D. Galloway (Tropical Animal Health and Production, 2006)

Identification of RAPD markers linked to the rust (Uromyces fabae) resistance gene in pea (Pisum sativum) - S. Vijayalakshmi; Kusum Yadav; Chanda Kushwaha; S. B. Sarode; C. P. Srivastava; Ramesh Chand; B. D. Singh (Euphytica, 2005)

Salinity-induced changes in peroxidase activity and cell-wall polysaccharides inVigna - Dipti S. Pujari; Sumitra V. Chanda (Journal of Plant Biology, 2003)

Effect of salinity stress on growth, peroxidase and IAA oxidase activities in vigna seedlings - D. S. Pujari; S. V. Chanda (Acta Physiologiae Plantarum, 2002)

Climate- and Human-Induced Woody Vegetation Changes in Botswana and Their Implications for Human Adaptation - S. RINGROSE; A. C. CHIPANSHI; W. MATHESON; R. CHANDA; L. MOTOMA; I. MAGOLE; A. JELLEMA (Environmental Management, 2002)

Alteration in growth and peroxidase activity by heavy metals in Phaseolus seedlings - N. G. Parmar; S. D. Vithalani; S. V. Chanda (Acta Physiologiae Plantarum, 2002)

Nitrate reductase activity of radish cotyledons as affected by phytohormones and different nitrogen sources - C. R. Sood; S. V. Chanda; Y. D. Singh (Acta Physiologiae Plantarum, 2000)

Effect of phytohormones and tungsten on light-induced and nitrate-induced nitrate reductase activity of mustard cotyledons - Sant Saroop; S. V. Chanda; Y. D. Singh (Acta Physiologiae Plantarum, 2000)

Glycosidases and acid-invertase activities are not correlated with Phaseolus hypocotyl growth - S. B. Bagatharia; S. V. Chanda (Acta Physiologiae Plantarum, 1998)

Light and nitrate induction of nitrate reductase in kinetin-and gibberellic acid-treated mustard cotyledons - Sant Saroop; V. S. Thaker; S. V. Chanda; Y. D. Singh (Acta Physiologiae Plantarum, 1998)

Effect of plant growth regulators and different nitrogen sources on NADP-isocitrate dehydrogenase activity of radish cotyledons - C. R. Sood; S. V. Chanda; Y. D. Singh (Acta Physiologiae Plantarum, 1998)

Modification of cell wall polysaccharides during cell elongation in Phaseolus vulgaris hypocotyls - S. B. Bagatharia; S.V Chanda (Acta Physiologiae Plantarum, 1998)

Changes in peroxidase and IAA oxidase activities during cell elongation in Phaseolus hypocotyls - S. B. Bagatharia; S. V. Chanda (Acta Physiologiae Plantarum, 1998)